Cineclube at School: Disseminating a Literary Culture from Actions of the ATLAS Project - Lucena, Mirelly Éllen Mendes de; Costa, Rodrigo; Santos, Jucelio (Anais do Workshop de Informática na Escola (WIE); 2019: Anais do XXV Workshop de Informática na EscolaDO - 10.5753/cbie.wie.2019.1244, 2019)
We aim to detect the habitual expectations of students and teachers in the use of procedures that address the interest in reading and favor their practice. We present a description of the activities carried out in one of the schools attended during the implementation of the ATLAS project, located in the municipality of Catole do Rocha, where it was proposed the adoption of a Cineclube in the teaching-learning process, aiming to provide a multidisciplinary vision that rescued student interest by practicing reading in a pleasant way. As a result, we observed that, we can encourage the participation of the student community in acquiring interest in the healthy habit of reading. We rescued the students search for the library as a stimulating and supportive space for learning; We permeate the curiosity of reading by students to investigate available materials such as books, newspapers, comics and other available media.